2014
DOI: 10.1158/0008-5472.can-14-1346
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Drives Radioresistance and Stroma-Driven Tumor Repopulation in Head and Neck Squamous Cancers

Abstract: Local control and overall survival in patients with advanced head and neck squamous cell cancer (HNSCC) remains dismal. Signaling through the Hedgehog (Hh) pathway is associated with epithelial-to-mesenchymal transition (EMT) and activation of the Hh effector transcription factor Gli1 is a poor prognostic factor in this disease setting. Here we report that increased GLI1 expression in the leading edge of HNSCC tumors is further increased by irradition where it contributes to therapy resistance. Hh pathway bloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 40 publications
3
50
2
2
Order By: Relevance
“…Studies showed that Gli-1 acts as a promoter as well as a transcriptional repressor of E-cadherin, an epithelial marker of de-differentiation, whereas the particular functions of different isoforms of Gli-1 have not been elucidated yet [34]. Contrasting our study, Gan and colleagues described contribution to radioresistance by Gli-1 in an in-vitro tumor model [35]. It has also been shown that Gli-2 expression was associated with cell death in mice that were treated with radiation therapy for intrahepatic carcinoma [36].…”
Section: Discussioncontrasting
confidence: 68%
“…Studies showed that Gli-1 acts as a promoter as well as a transcriptional repressor of E-cadherin, an epithelial marker of de-differentiation, whereas the particular functions of different isoforms of Gli-1 have not been elucidated yet [34]. Contrasting our study, Gan and colleagues described contribution to radioresistance by Gli-1 in an in-vitro tumor model [35]. It has also been shown that Gli-2 expression was associated with cell death in mice that were treated with radiation therapy for intrahepatic carcinoma [36].…”
Section: Discussioncontrasting
confidence: 68%
“…32,33 However, transient Hh activation in salivary glands, such as overexpression of Gli1 transgene for 15 weeks and overexpression of Shh transgene for 1 week, did not result in any detectable tumor in mice. 15,34 Gene therapy for salivary gland hypofunction has several unique advantages, including easy access to most parenchymal cells via duct cannulation, the capacity to produce high amounts of protein, and tight encapsulation that minimizes concern about transgene spread.…”
Section: Discussionmentioning
confidence: 98%
“…These investigations show increased response to radiation in CSCs after inhibition of CHEK1/2 and application of ATRA (Bertrand et al 2014). Inhibition of SHH/MTOR/RPS6KB1 pathways leads to increased radiosensitivity in CSCs, suggesting a role for these pathways and potential targetable options for increasing CSC radiosensitivity (Gan et al 2014).…”
Section: Increasing Csc Sensitivity To Chemotherapy and Radiationmentioning
confidence: 99%